What's new in Argentina? New scholarship on Argentinian Jewish diaspora (KULT_online, 2013)
The authors of The New Jewish Argentina. Facets of Jewish Experiences in the Southern Cone offer readers an interesting and well-researched book on Jewish past and current-day experience in Argentina.  Their contributions on Argentinean Jewish literature, cinema, history, and society constitute an excellent mixture, allowing us to track the most recent developments in the Latin American Jewish studies. Especially interesting is the focus on minority discourses formerly largely neglected by the scholarship.